Verstaat gij wat gij vertaalt?: AI als vertaalhulp voor verschillende typen vertaling - Amersfoort, Thijs (Kerk en theologie, 2026)
This article explores the use of large language models as a tool in Bible translation, with specific attention to the strengths and weaknesses of the application of AI to specific translation types. Building on the first results from research into AI-assisted translations in plain language (such as the Dutch Bijbel in Gewone Taal), the study compares these findings with a case study on AI use in a more literal study translation (the Nieuwe Concordante Vertaling). The analysis shows that while AI can accelerate and assist in translation, analysis, and annotation, its limitations differ per translation type, making human oversight indispensable.